Financial distress analysis uses the modified Altman z-score method at PT. Prasidha Aneka Niaga Tbk for the 2019-2021 period - Seleky, Roy; Christianty, Restia; Latuconsina, Zainuddin (ProBisnis : Jurnal Manajemen, 2024)
The purpose of this study was to determine the financial condition of Perum Perumnas Regional-1 Medan using the Altman Z-score method. The data analysis technique used in this study was descriptive analysis technique, namely collecting data, classifying data, explaining data and analyzing data. The results of the study show that with the Altman Z-score method, companies experience financial distress every year.